Adaptations of provincial high school student-athletes transitioning to a Metro Manila-based college sports program an exploratory study - Paurom, Tito Vincent V. 2000-; Callanta, Hercules P. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Academic institutions in the capital of the Philippines attract student-athletes from all around the country. This move is motivated by the schooling and economic opportunities presented by urban areas such as Metro Manila (UNESCO, 2018). Consequently, relocated student-athletes from the province are plagued by abrupt changes in their environment and tough demands. In place, previous researchers have studied the relocation of college student-athletes and its implications on their overall wellbeing. However, there is a lack of research regarding the interregional relocation of student-athletes in the Philippines. With that being said, this research explores the adaptation experiences of college student-athletes within a university in Metro Manila, provided that they previously lived in areas outside the capital before going to college. Guided by an interpretivist approach, semi-structured interviews were conducted on six (6) participants fitting the description. The key themes that emerged included Adaptation Challenges, Coping and Resilience, and Support Systems. The findings suggest that understanding the interrelationship between the three main themes are essential for creating support systems that work for relocated student-athletes
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: College athletes -- Recruiting; Student adjustment